From social exclusion to adult education and training for community development in South Africa. Issue 4 (8th August 2018) - Mayombe, Celestin
ABSTRACT: In South Africa, adult education and training (AET) programs are a new frontier in the process of community development and strategies to reduce poverty and social exclusion. This article focuses on how AET graduates perceived the impact of the AET programs on their living conditions after graduating, getting paid jobs, or creating their own microenterprises. Using both quantitative and qualitative research methods, the main findings reveal that the impact of paid jobs or microenterprises on the living conditions of graduates was related to becoming self-sufficient and living with dignity after graduating. Based on the findings, the author concludes that AET programs for poor and unskilled adults can reduce social exclusion caused by unemployment and poverty and, hence, contribute to community development.